2023
DOI: 10.55284/ajel.v8i1.890
|View full text |Cite
|
Sign up to set email alerts
|

Guided-blended collaborative learning in speaking class: Voices of non-native English teachers and students from eastern Indonesia

Abstract: The purpose of this qualitative study is to explore and address two important questions from ten qualified non-native English teachers and five students who have been actively involved as research participants: (1) how non-native English teachers help students improve their English speaking performance through guided-blended collaborative learning, and (2) how non-native English teachers and students view guided-blended collaborative learning as a way of improving students’ English speaking performance. Based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It was also concluded that there are separate speaking components that students need to manage, such as taking turns, rephrasing, providing feedback, and redirecting [2]. They also need to concentrate on the success of the interaction as well as adjust speech components such as vocabulary, tempo, and complexity of grammar structures to improve listeners' comprehension and involvement [3], [26][27].…”
Section: Resultsmentioning
confidence: 99%
“…It was also concluded that there are separate speaking components that students need to manage, such as taking turns, rephrasing, providing feedback, and redirecting [2]. They also need to concentrate on the success of the interaction as well as adjust speech components such as vocabulary, tempo, and complexity of grammar structures to improve listeners' comprehension and involvement [3], [26][27].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, teachers' roles and responsibilities as facilitators also include adopting certain paradigms and mindsets to manage students' learning processes. This includes reflecting on what has been done to increase student participation (Butarbutar, Ruing, et al, 2023;Butarbutar, Weda, et al, 2023; in speaking activities. In this vein, BSD's findings have been empirically supported.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In the context of teaching EFL, Motlagh et al (2023) revealed that blended collaborative learning contributed to better performance of students' English reading comprehension especially in terms of understanding the concept of English texts and using proper vocabulary to complete the texts. Butarbutar et al (2023) found that blended collaborative learning was successful to implement in teaching speaking English as a foreign language. Moreover, technology in blended collaborative learning supported students to be more self-directed and independent.…”
Section: Introductionmentioning
confidence: 99%